Yield and cold storage of Trichoderma conidia is influenced by substrate pH and storage temperature. (17th February 2017) - Steyaert, Johanna M.; Chomic, Anastasia; Nieto‐Jacobo, Maria; Mendoza‐Mendoza, Artemio; Hay, Amanda J.; Braithwaite, Mark; Stewart, Alison
Abstract : In this study we examined the influence of the ambient pH during morphogenesis on conidial yield of Trichoderma sp . "atroviride B" LU132 and T. hamatum LU593 and storage at low temperatures. The ambient pH of the growth media had a dramatic influence on the level of Trichoderma conidiation and this was dependent on the strain and growth media. On malt‐extract agar, LU593 yield decreased with increasing pH (3–6), whereas yield increased with increasing pH for LU132. During solid substrate production the reverse was true for LU132 whereby yield decreased with increasing pH. The germination potential of the conidia decreased significantly over time in cold storage and the rate of decline was a factor of the strain, pH during morphogenesis, growth media, and storage temperature.